Znanje o multikulturnih tematikah in zmanjševanje predsodkov - Klemenčič, Eva (Šolsko polje, 2011)
Despite the different directions of theoretical and fermentation patterns in intercultural education, unity is the fact that intercultural education is a necessary response to the challenges of the modern globalized world. The paper theoretically illuminates targets and the importance of intercultural education in its diff erent dimensions and contexts, which have an impact on the development of the modern citizens' empowerment to cope successfully with remaining in the modern multicultural world. Based on secondary analysis of the data from International Civic and Citizenship Education Study (ICCS 2009), we examined the impact of various contexts on the knowledge of multicultural themes and the correlation of the prejudices held by pupils on multicultural topics. Based on collected empirical data, we can confirm that the knowledge of multicultural topics is related to reducing the prejudice of multicultural themes.
Keywords: education; vzgoja in izobraževanje; knowledge; državljanska vzgoja; multiculturalism; medkulturna vzgoja; ICCS 2009; prejudice; znanje; multikulturalizem; predsodki; mednarodne raziskave